Effective coaching in strength and conditioning. The foundations of the profession - Collins, D.; Moody, J. (Routledge, 2016)
We would like to attempt a conceptualisation of some of the keys areas that are often overlooked when we observe the discipline area of strength and conditioning (S&C) and, perhaps more importantly, the process (and indeed processes) of the S&C coach. We would suggest that S&C coaches across the continuum of development consider the following content as part of the role whilst digesting the fabulous information provided by such highly rated applied professionals in the following chapters. Initially we would like to scope the role and purpose of the S&C coach with regard to the dearth of information about contributory factors that may affect this. It is a bold attempt to confirm the requirement of clarity and direction, with a bundle of accountability concerns that accompany such expectations. The chapter also explores how S&C coaches should work, the environments they work in, and the associated challenges such environments will demand. Often overlooked are the ancillary knowledge and the importance of the `soft` skill set within the coaching sector; after all, the job title in the majority of cases does mention the word `coach`. Finally, there is a closer inspection of the thinking process(es) that may be required as part of the delineated role.